NOx software sensor - BARBE THIERRY; AMMOURI FOUAD (2007)
Methods and apparatus for determining the NOx content in a combustion flue gas. Several parameters of the combustion process are measured in the combustion furnace. These parameters are then input to a neural network, which then, based upon the input data, generates output data representative of the concentration of NOx in the flue gas. This result is determined without the use of physical NOx sensors.